Hubungan Anemia dengan Kejadian Berat Badan Lahir Rendah di Puskesmas Sungai Durian Kabupaten Sintang - Gesti Kiki Okta; Siti Fadhilah; Yunri Merida (Jurnal Siti Rufaidah, 2025)
Anemia in pregnant women is a health problem that contributes significantly to Low Birth Weight (BBLR), a serious issue in Indonesia with a prevalence exceeding 15% according to WHO, and is a major contributor to the high Neonatal Mortality Rate. This study aims to examine the relationship between anemia in pregnant women and the incidence of BBLR at the Sungai Durian Health Center, Sintang Regency. Using a case control analytical research design with secondary data from medical records in 2024, the sample used was 116 respondents, consisting of 58 pregnant women with BBLR babies as the case group and 58 pregnant women with normal birth weight babies (BBLN) as the control group, which were taken by total sampling technique. Data analysis was carried out using the Chi-Square test and the Odds Ratio (OR) with a significance level of 95%. The results of the study show that the incidence rate of BBLR at the Sungai Durian Health Center in 2024 is 25.8%, and the incidence of anemia in pregnant women is 46.6%. Statistical tests showed a significant relationship between anemia in pregnant women and the incidence of BBLR (p < 0.05). Pregnant women with anemia had a 21.758 times greater risk of giving birth to a BBLR baby compared to non-anemic mothers (OR=21.758; CI 95% = 1.45–7.08). The study concluded that there was a relationship between the nutritional status of pregnant women and the incidence of preeclampsia at the Sungai Durian Sintang Health Center.